2019
DOI: 10.1371/journal.pone.0215955
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and mitochondrial uncoupling protein 2 expression in hepatic steatosis induced by exposure to xenobiotic DDE and high fat diet in male Wistar rats

Abstract: Oxidative stress plays a key role in steatohepatitis induced by both xenobiotic agents and high fat diet (HFD). The present study aimed to evaluate hepatic oxidative stress and anti-oxidant systems response in rats exposed to HFD and/or non-toxic dose of dichlorodiphenyldichloroethylene (DDE), the first metabolite of dichlorodiphenyltrichloroethane. Groups of 8 rats were so treated for 4 weeks: 1- standard diet (N group); 2- standard diet plus DDE (10 mg/kg b.w.) (N+DDE group); 3- HFD (D group); 4- HFD plus DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 75 publications
4
43
0
Order By: Relevance
“…MDA levels increased more under DDE administration, without significant differences between N + DDE (9.71 ± 0.16 nmol) and HF + DDE (9.42 ± 0.49 nmol) groups. In liver, MDA accumulation showed the same trend observed in kidney, with the highest levels of peroxides in DDE‐treated groups, no matter the diet . However, lipid peroxidation in liver was greater than kidney, in all the groups considered; the main differences were found between DDE‐treated groups, being MDA values in liver about 2‐fold higher than in kidney …”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…MDA levels increased more under DDE administration, without significant differences between N + DDE (9.71 ± 0.16 nmol) and HF + DDE (9.42 ± 0.49 nmol) groups. In liver, MDA accumulation showed the same trend observed in kidney, with the highest levels of peroxides in DDE‐treated groups, no matter the diet . However, lipid peroxidation in liver was greater than kidney, in all the groups considered; the main differences were found between DDE‐treated groups, being MDA values in liver about 2‐fold higher than in kidney …”
Section: Resultssupporting
confidence: 58%
“…In addition, it has been demonstrated that the increase of lipid peroxides is associated to an inhibition of MT synthesis in rat testis . Since our data indicate a hepatic increase of lipid peroxidation following HF‐ and/or DDE‐treatments, it is conceivable that also in the liver lipid peroxides are able to affect MT expression and synthesis, no matter if the peroxides are produced by the dietary fat or the pesticide.…”
Section: Discussionmentioning
confidence: 51%
“…Recently, histological and molecular analysis indicated that oral exposure to a moderately low dose of DDE (10 mg/kg bw) for 4 weeks was able to elicit morphological alterations, cellular oxidative stress, and lipid peroxidation in rat tissues [47,48,56,58]. Studies also evidenced the presence of similar morphological and oxidative damage caused by the fat diet alone [47,48,56,58]. In the liver, an HF diet induced steatosis of hepatocytes, and DDE treatment-tissue inflammation and cellular vacuolization.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that cells activated the endogenous antioxidant system to protect themselves from the oxidative damage generated in HF-and DDE-treated animals. In particular, increased synthesis and enzymatic activity of SOD1/2 and total GPx antioxidant enzymes and the induction of the mitochondrial uncoupling protein 2 (UCP2) were observed in the hepatocytes the to limit the mitochondrial damage produced by ROS [47,56]. On the contrary, testicular cells showed antioxidant system impairment in the HF-and DDE-treated animals associated with an increase in lipid peroxidation and the apoptotic rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation